Game-Based Learning dalam Pembelajaran Pantun di SD/MI: Eksplorasi Media Ular Tangga untuk Keaktifan dan Keterlibatan Siswa Kelas V - Adinda Nurhabibah Nasution; Munawir; Taufik; Nur Romdlon Maslahul Adi; Nuril Kartika (Journal of Practice Learning and Educational Development, 2026)
The teaching of pantun in elementary schools (SD/MI) has been found to still employ conventional, monotonous teaching methods, resulting in students becoming less enthusiastic, experiencing difficulties in composing pantun according to the rules, and lacking involvement in the learning process. This study aims to describe the implementation of snakes and ladders as a form of Game-Based Learning (GBL) in teaching pantun in fifth grade, analyze the role of teachers in the process, and identify forms of student activity and engagement. The research method used in this study is a qualitative approach with a case study design. Data were obtained through observation, teacher reflective journals, and interviews with students. The results of the study indicate that the pantun snake and ladder game is effective in creating an active, collaborative, and enjoyable learning atmosphere. Teachers play the role of facilitators, guides, and motivators, maintaining a balance between the structure of learning and the flexibility of the process. Student engagement is reflected in active participation in answering questions, group discussions, and healthy competitive spirit. Most students (around 90%) were able to compose pantun independently according to the rules and rhymes. This GBL strategy successfully fostered students' interest, creativity, and understanding of pantun. These findings recommend the integration of traditional game media in literature learning to improve cultural literacy and learning effectiveness at the elementary school level.